MAKASSAR HEADDRESSED PASSAPU/PADOMPE - Dian Cahyadi; Karta Karta (Universitas Negeri makassar, 2019)
This study aimed to identify artifacts of cultural products in the community within the Makassar ethnic scope related to various forms, characteristics (identification tools) formed from the results of intangible cultural products. The identification of cultural products is intended to make the perimeter boundaries of culture as a feature. The specific purpose of this research is to identify the form of 'Passapu' in Makassar ethnic which is known for its various names and forms, by describing the differences and reviewing the aspects and their constituent elements (Anthropology / Sociology of Art Review). The results of this research identification are expected to become scientific reference material on intangible cultural outcomes for ethnic Makassarese.